ROS1 Expression Correlates With Inguinal Lymph Node Affection in Vulvar Cancer Patients: A Retrospective Study - Meletios P. Nigdelis; Annick Bitterlich; Mariam Parvanta; Bashar Haj Hamoud; Erich Franz Solomayer; Martin Ertz; Laura Schnöder; Annette Hasenburg; Bernd Holleczek; Mathias Wagner; Gilbert Georg Klamminger (Cancer Medicine)
ABSTRACT Purpose Systemic treatment options for vulvar squamous cell carcinoma (VSCC) are limited. ROS1, a tyrosine kinase implicated, for example, in non‐small cell lung cancer (NSCLC), has recently shown responsiveness to tyrosine kinase inhibitors. This study investigated immunohistochemical ROS1 expression in VSCC to explore its potential as a future therapeutic target in this rare malignancy. Methods In this retrospective study, 48 patients with VSCC undergoing vulvectomy were included. Clinicopathological data were collected in a standardized manner. Immunohistochemistry (IHC) was used to assess ROS1 expression on an ordinal scale from 0 (absent staining) to 3 (> 50% of neoplastic cells demonstrated cytoplasmatic staining); levels 0 and 1 were considered negative, while 2 and 3 were rated as positive. After differences and correlations with clinicopathological parameters were evaluated between positive and negative tumors, we fitted logistic regression and survival models to assess the association of ROS1 with inguinal lymph node involvement and overall survival. Statistical analysis was conducted using GraphPad and Jamovi. Results ROS1 IHC levels were associated with lymph node involvement [odds ratio (OR) 2.396, 95% confidence interval (CI) 1.034–5.555, logistic regression, p = 0.042]. ROS1 positive tumors demonstrated no difference in overall survival compared with negative ones [hazards ratio (HR) 0.837, 95% CI 0.283–2.479, log‐rank (Mantel‐Cox) test, p = 0.738]. Conclusion ROS1 expression was associated with inguinal lymph node involvement but not overall survival among VSCC patients. Further studies are required to elucidate the role of ROS1 in VSCC therapeutics.